All Days 2010
DOI: 10.4043/20907-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improve Offshore Heavy Oil Recovery by Compound Stimulation Technology Involved Thermal, Gas and Chemical Methods

Abstract: Heavy oil resource is three times of conventional oil in Bohai oilfield - the largest offshore oilfield in China. The heavy oil reservoirs are deposited at depth from 900m to 1900m with high permeability (up to 5000mD), large thickness (5 to 30 meters), conventional heavy oil viscosity(usually below 2000 mPa·s under reservoir conditions). Some heavy oil reservoirs are produced by electrical submersible pumps (ESP) in past years, and very low oil production is obtained after short considerable oil production pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…By injecting a compound fluid of steam-flue gas or CO 2 /N 2 -chemical agents, multi-component thermal fluids stimulation technology can improve the recovery of heavy oil efficiently (Hornbrook et al 1991;Liu et al, 2010;Sun et al, 2011;Tang et al, 2011;Gu et al, 2012;Jiang et al, 2012). Because the needed equipments and apparatus have small volume and can be handled easily, multicomponent thermal fluids stimulation technology are a feasible way to recover offshore heavy oil reservoirs.…”
Section: Introductionmentioning
confidence: 97%
“…By injecting a compound fluid of steam-flue gas or CO 2 /N 2 -chemical agents, multi-component thermal fluids stimulation technology can improve the recovery of heavy oil efficiently (Hornbrook et al 1991;Liu et al, 2010;Sun et al, 2011;Tang et al, 2011;Gu et al, 2012;Jiang et al, 2012). Because the needed equipments and apparatus have small volume and can be handled easily, multicomponent thermal fluids stimulation technology are a feasible way to recover offshore heavy oil reservoirs.…”
Section: Introductionmentioning
confidence: 97%
“…1 cycle N 2 injecting volume is 21 Â 10 4 m 3 ; the cycle CO 2 injecting volume is 3.7 Â 10 4 m 3 ; the cycle steam injecting volume is 480 t. After operation, the average water cut of this well is reduced by about 27.2%, and the oil daily rate is increased from 2.8 t to 10.1 t. The cumulative oil increment is about 1009 t. Considering the successful operation of multi-thermal fluid stimulation technique in this well, two well groups in C20 block of Shengli oilfield have been operated as the new testing sites. In 2010, multi-thermal fluid stimulation technique is also introduced into the development of NB35-2S heavy oil block of Bohai offshore oilfield in China (Liu et al, 2010(Liu et al, , 2011Sun et al, 2011;Yu et al 2014), as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 97%
“…At present, the multithermal fluid technology has been applied in oilfield. In Bohai Oilfield, China, due to the limitation of the offshore platform area, the conventional technology based on steam injection is unsuitable and the multithermal fluid technology was introduced [11][12][13]. The field results show high oil recovery and good economic benefit.…”
Section: Introductionmentioning
confidence: 99%